Adoption of strategic management tools in pedagogical routines at an elementary school in Rondon do Pará (Revista Contexto & Educação, 2025)
This research aims to investigate how strategic planning tools can incorporated into the pedagogical routines of an educational institution to promote excellence in teaching. Aims to understand the role of these tools in the continuous improvement of educational quality, supporting school management, and optimizing the decision-making process. A qualitative case study in a public elementary school for the final years, located in Rondon do Pará-PA. The research employed semi-structured interviews to collect data and perceptions from those involved, providing a detailed analysis of administrative and pedagogical practices. Highlights the importance of implementing management strategies in non-business environments. The findings contribute significantly to the field of education, introducing innovative methods of management and decision-making. Furthermore, it expands the practical scope of administration by strengthening the relationship between administrative theory and educational practice. Reveals how strategic management tools, traditionally used in the business sector, can be adapted by education professionals without specific training in administration. Familiarization with these tools allows educators to observe the specific needs of the school and choose the most appropriate one, facilitating the implementation and effectiveness of educational projects throughout the academic year.
Keywords: Strategic planning; School management; Pedagogical political project